Fatores que contribuem para a não realização do exame de prevenção do câncer cérvico uterino, no município de Cianorte - PR - Domingos, Andréia Cristiane Pizani (2008)
Cervical Cancer represents the second most common cause of death of women in Brazil. Cervical cancer has an incidence of about half million cases a year in the world, especially in developing countries. This study aims at identifying possible factors why women do not have routine pap smears for cervical cancer performed in the city of Cianorte-Pr. The work is characterized by a survey study, out applied by means of population inquiry. The research was performed in the city of Cianorte-Pr, northwest of Paraná, Brazil. The sample totality 427 women. For the selection of addresses and the interviews, the map of the city was obtained from the city hall. The collection of data was performed by means of a questionnaire. For the selection of interviewed women, the interviewer started the way in the first house of the first street of the village, skipped two houses and interviewed the next one. In case of not finding women in the age studied or a closed house, the next one was interviewed. The research had the approval of the ethics committee of the Universidade Estadual de Maringá (COPEP). Results obtained: women in the 40s, menstruated at the age of 13, initiated the sexual life at an average age of 19, don't smoke, are married, have a regular partner, 40,98% incomplete elementary school, had two or three children born in normal or cesarean birth, do not use condoms and most of them affirmed not having had a sexually transmitted disease (STD) in the last ten years. Of the women who reported to have had some STD, the most cited was HPV. As for gynecological infections, 64% had already presented this problem, but did not need cauterization and 54% had never had any kind of cancer in the family. As for contraceptive methods, 56% of women did not use any and among women who used them, the methods were pills and surgery. About the preventive examinations, 92% had already had them performed. Of those, 73% reported to have felt no pain in the procedure and 48,84% had some difficulty during its performance. Just 8% had never been submitted to the exam, 30% percent do not do it regularly and 53% do it annually. Of the women who do it, 72,26% do it because of their own will. The main reason for not doing it was for comodity, followed by fear or shame. Women who had children had the exam done more often. Among the difficulties found for the performing of the exam, women who make use of public health service had more difficulty. Married women do it more than single women and, because they have regular partners, don't think condoms are necessary. As a conclusion, it was possible to notice that many of the interviewed women perform the preventive exam in private clinics or do not do it regularly, which may explain the low municipal cover of the Program of Prevention of Gynecological Cancer. As a solution we suggest campaigns for making people aware of its importance and different times of collection.